Islamic Banks’ Risks and Profitability A Case Study on Islamic Banks in Indonesia - Sutrisno, Sutrisno (KINERJA, 2020)
The development of Islamic banks shows excellent growth in terms of assets, third party funds, and financing. However, the growth of Islamic banks, which is approximately 5%, is relatively small nationally. For this reason, researches on Islamic banks always attracts attention. The purpose of this study is to analyze the factors that influence the profitability of Islamic banks. The profitability of Islamic banks is measured using return on assets (ROA), while the factors suspected of affecting profitability are capital risks are measured using the capital adequacy ratio (CAR), financing risk is measured using non-performing financing (NPF), operating risk is measured using operational costs to operational income ratio (OCOI), and company’s size (SZ). The population of this study is 13 Islamic banks with a sample of 7 banks implementing a purposive sampling method. The observation period is 8 years (2011-2018), with quarterly data. The analysis tool to test the hypotheses is multiple regression. The results showed that capital risk (CAR) had a significant but negative effect on profitability, operating risk (OCOI) had a significant but negative effect. While financing risk (NPF) and company’s size (SZ) had no significant effect on profitability.Keyword: capital risks, financing risks, operational risks, profitability